(untitled) (LEARNing Landscapes, 2015)
Thinking narratively (Clandinin, 2013), we inquire into our ongoing personal and professional development within the shaping of a nested community. By traveling to diverse worlds (Lugones, 1987), we attend to some of our stories to live by (Connelly & Clandinin, 1999) and illuminate how living and telling stories within our community shapes and reshapes who we are and are becoming as narrative inquirers. Holding tensions and possibilities close, we create(d) a space where we can be ourselves and can personally and professionally learn alongside one another. It is both a safe space of coming home and starting new journeys.